CAN THE SMALL-SCALE PRODUCERS OF NAVEL ORANGE RESIST THE STABILITY OF THE FARM GATE PRICES AND THE SOAR OF THE INPUT PRICES WITHIN THE BIOPHYSICAL FACTORS? - Mohamed, Assem A. A.; Esmail, A. A. M.; Abdelaty, Emad F. (Socio-Economics/Agribusiness Department, 2024)
Egypt Navel orange planted area reached about 174.6 thousand acres during the average period of 2012-2020. Delta governorates is the major orange’s productive region in Egypt with 97.4% of the total production of the country. 87.2% of orange’s planted area came from only five Delta governorates. The top planted area governorates are El Behera with an acreage area representing about (41.3%), followed by Qalyoubia (16.7%), Ismailia (11.1%), Menufia (9.54%) and Sharqiya (8.52%) of total planted areas during the period 2012-2020. El-Behera is the major Navel orange’s productive governorate in Egypt with (43.9%) of Egyptian total production of Navel orange, followed by Qalyoubia (18.8%), Menufia (9.2%), Ismailia (8.3) and Sharqiya (7.7%) of Navel orange total production during the period 2012-2020. In recent years, small scale farmers have experienced technical, environmental and economic problems. This study will shade light on the economic problems because fruit prices have come to a standstill or even decreased while the production costs have risen continuously. The present study depends on data collected from the private small farm planted with Washington Navel orange trees [Citrus sinensis L.(Osbeck)] since 1968, which is located in Minyat as Siba, Benha-Qalyoubia governorate, Egypt. The result shows that the average values of fertilizers, pests and diseases account for a large proportion of the total costs, representing about 42.57% and 26.47% respectively from the total production costs during 2012-2022. Prices received for Navel oranges fluctuate markedly from year to year. This combined with fluctuations in yields. Over the period 2012 to 2022 farm gate prices of Navel orange averaged 2905 Egyptian pound (LE) per ton, with the minimum of LE 1750 per ton in 2012 and the maximum of LE 4000 per ton in the 2019, 2020 and 2021.